Exploring the eukaryotic Yip and REEP/Yop superfamily of membrane-shaping adapter proteins (MSAPs): A cacophony or harmony of structure and function? - Angelotti, Timothy (Frontiers in Molecular Biosciences, 2022)
Polytopic cargo proteins are synthesized and exported along the secretory pathway from the endoplasmic reticulum (ER), through the Golgi apparatus, with eventual insertion into the plasma membrane (PM). While searching for proteins that could enhance cell surface expression of olfactory receptors, a new family of proteins termed “receptor expression-enhancing proteins” or REEPs were identified. These membrane-shaping hairpin proteins serve as adapters, interacting with intracellular transport machinery, to regulate cargo protein trafficking. However, REEPs belong to a larger family of proteins, the Yip (Ypt-interacting protein) family, conserved in yeast and higher eukaryotes. To date, eighteen mammalian Yip family members, divided into four subfamilies (Yipf, REEP, Yif, and PRAF), have been identified. Yeast research has revealed many intriguing aspects of yeast Yip function, functions that have not completely been explored with mammalian Yip family members. This review and analysis will clarify the different Yip family nomenclature that have encumbered prior comparisons between yeast, plants, and eukaryotic family members, to provide a more complete understanding of their interacting proteins, membrane topology, organelle localization, and role as regulators of cargo trafficking and localization. In addition, the biological role of membrane shaping and sensing hairpin and amphipathic helical domains of various Yip proteins and their potential cellular functions will be described. Lastly, we will discuss the concept of Yip proteins as members of a larger superfamily of membrane-shaping adapter proteins (MSAPs), proteins that both shape membranes via membrane-sensing and hairpin insertion, and well as act as adapters for protein-protein interactions. MSAPs are defined by their localization to specific membranes, ability to alter membrane structure, interactions with other proteins via specific domains, and specific interactions/effects on cargo proteins.